The Associations Between Cultural Identity and Mental Health Outcomes for Indigenous Māori Youth in New Zealand - Williams, Ashlea D.; Clark, Terryann C.; Lewycka, Sonia (Frontiers in Public Health, 2018)
Objectives: To explore the relationships between Māori cultural identity, ethnic discrimination and mental health outcomes for Māori youth in New Zealand. Study Design: Nationally representative, anonymous cross-sectional study of New Zealand secondary school students in 2012. Methods: Secondary analysis of Māori students (n=1699) from the national Youth’12 secondary school students survey was undertaken. Theoretical development and exploratory factor analysis were undertaken to develop a 14-item Māori Cultural Identity Scale (MCIS). Māori students reporting > 8 items were classified as having a strong MCIS. Prevalence of indicators were reported and logistic regression models were used to explore how wellbeing (WHO-5), depressive symptoms (Reynolds Adolescent Depression Scale-SF), and suicide attempts were associated with the MCIS. Results: After adjusting for age, sex, ethnic discrimination and NZ Deprivation Index (NZDep), a strong Māori cultural identity (MCIS) was associated with improved wellbeing scores (OR 1.53, 95% CI 1.18 – 2.01) and fewer depressive symptoms (OR 0.53, 95% CI 0.38 - 0.73). Experiencing discrimination was associated with poorer wellbeing scores (OR 0.50, 95% CI 0.39 – 0.65), greater depressive symptoms (OR 2.2, 95% CI 1.55 – 3.18), and a previous suicide attempt (OR 2.47, 95% CI 1.71 – 3.58). Females less frequently reported good (WHO-5) wellbeing (OR 0.33, 95% CI 0.26-0.42), increased (RADS-SF) depressive symptoms (2.61, 95% CI 1.86-3.64) and increased suicide attempts (OR 3.35 (2.07-5.41) compared to males. Wellbeing, depressive symptoms and suicide attempts did not differ by age or neighbourhood level socio-economic deprivation, except those living in neighbourhoods characterised as having medium level incomes, were less likely to have made a suicide attempt (OR 0.49, 95% CI 0.27-0.91). Conclusions: Māori youth who have a strong cultural identity were more likely to experience good mental health outcomes. Discrimination has a serious negative impact on Māori youth mental health. Our findings suggest that programmes, policies and practice that promote strong cultural identities and eliminate ethnic discrimination are required to improve mental health equity for Māori youth.